The Influence of Performance Status, Inflammation, and Nutrition on the Impact of SGLT2 Inhibitors on Cancer Outcomes - Diego Rivas‐Otero; Tomás González‐Vidal; Pablo Agüeria‐Cabal; Guillermo Ramos‐Ruiz; Paula Jimenez‐Fonseca; Carmen Lambert; Pedro Pujante Alarcón; Edelmiro Menéndez Torre; Miguel García‐Villarino; Elías Delgado Álvarez (Cancer Medicine)
ABSTRACT Background Sodium–glucose‐linked transporter 2 inhibitors (SGLT2i) may have antitumor effects. Previous studies analyzing their role in mortality and progression did not account for potential confounders, including cancer treatment, performance status, inflammatory markers, and nutritional status. This study aims to evaluate the impact of SGLT2i treatment on mortality and progression while considering these potential confounders. Methods A retrospective cohort study was conducted. A total of 526 patients with cancer (302 women, mean age 64 years, range 40–79 years) were divided into two cohorts based on whether they were taking SGLT2i at the time of their cancer diagnosis and followed for 1 year or until death. All patients on SGLT2i were taking these drugs at standard clinical doses. Additional data collected included basic demographic variables, metabolic and lifestyle characteristics, cancer treatment received, performance status, inflammatory markers, and nutritional status. The primary endpoints were mortality and progression. Results Patients taking SGLT2i at the time of cancer diagnosis (n = 41) were more likely to have type 2 diabetes, to be male, to be ever‐smokers, and to be older than patients not taking SGLT2i. In univariate analyses, SGLT2i treatment at the time of cancer diagnosis was not associated with mortality or cancer progression. Instead, mortality and cancer progression were positively associated with a diagnosis of T2D, male sex, older age, heavy alcohol drinking, ever‐smoker status, poor performance status, increased inflammation, malnutrition, tumor site, cancer stage, and lack of cancer treatment. After adjusting for these potential confounders, SGLT2i treatment was not significantly associated with mortality or cancer progression. Conclusions Our results suggest that the impact of SGLT2i treatment on cancer outcomes is limited under standard clinical dosing conditions.